2012
DOI: 10.1007/s00264-011-1445-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of infectious discitis. Outcome in one hundred and eight patients in a University Hospital

Abstract: Purpose The optimal management of pyogenic discitis is not agreed on. We conducted a retrospective, cross-sectional, observational study in which all patients with discitis who attended Hospital San Carlos Madrid from January 1999 to January 2009 were included. Methods We identified 108 consecutive adult patients with infectious discitis. There were 49 men and 59 women with an average age of 67,5 (+/-16,89) years in the study group. Mean follow-up interval was 6,06 (12,5-2) years. 78 patients had spontaneous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 22 publications
(35 reference statements)
4
49
3
Order By: Relevance
“…The reported systemic antibiotic treatment duration ranged between 6 and 40 weeks [4,30,35]. Despite antibiotic treatment, additional surgery was required in 25-55 % of the reported cases [4,30]. Relapse rates of 2 and 4 % after antibiotics treatment only were reported in two studies.…”
Section: Outcomes Of Systemic Antibiotic Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The reported systemic antibiotic treatment duration ranged between 6 and 40 weeks [4,30,35]. Despite antibiotic treatment, additional surgery was required in 25-55 % of the reported cases [4,30]. Relapse rates of 2 and 4 % after antibiotics treatment only were reported in two studies.…”
Section: Outcomes Of Systemic Antibiotic Treatmentmentioning
confidence: 99%
“…Four studies were of a more descriptive nature and reported the outcome after antibiotic therapy [4,30,35,37]. The reported systemic antibiotic treatment duration ranged between 6 and 40 weeks [4,30,35]. Despite antibiotic treatment, additional surgery was required in 25-55 % of the reported cases [4,30].…”
Section: Outcomes Of Systemic Antibiotic Treatmentmentioning
confidence: 99%
See 3 more Smart Citations